The Dynamic Relationship between Export, Import and Inflation: Empirical Evidence from India. Issue 3 (December 2018) - Sahoo, Malayaranjan; Sethi, Narayan
This article aims to examine the relationship between inflation, export, import and foreign direct investment (FDI) in India from1975 to 2017. The study employed Johansen co-integration test to find out the long-run relationship among the variables and further variance decomposition analysis (VDA) and impulse response function (IRF) through vector autoregression (VAR) used to find out the dynamic relationship. Both VDA and IRF results indicate that export has positive or greater influence in inflation in India than other variables like import and FDI. The pair-wise granger causality approach finds that there is unidirectional causality running between exports and inflation and not vice versa, whereas inflation granger causes import. Toda Yamamoto causality also has shown similar result. Both the causality tests revealed that no causal relationships exist between inflation and FDI in India during the study period. As the exports of India have been continuously declining for past few years, the outcomes of this study are the true depiction of India's economic situation. So, the government should provide a competitive environment and incentives to the local industry to produce at competitive prices to the international market.